Nationalism And Islamism In The Kurdistan Region Of Iraq – The Emergence Of The Kurdistan Islamic Union: A Critical Review - Dr.Neville D’Cunha (International Journal of Modern Agriculture, 2021)
This article is a review of a book published in the Routledge Studies in Middle Eastern Politics. The book under review, Nationalism and Islamism in the Kurdistan Region of Iraq: The Emergence of the Kurdistan Islamic Union, addresses timely and troubling issues in our democratic political discourse related in one way or another to the interface between religion and politics in the context of Islamic political parties. A diversity of specific topics is covered including Islam, religious nationalism, Kurdistan Region, democracy, and Kurdistan Islamic Union (KIU), pertinently in the shadow of Kurdistan’s lack of statehood. This review aims to explore the interconnection between all these concepts and most specifically the interrelationship of religion and nationalism and how it has been perceived and practiced by the Islamic political party called Kurdistan Islamic Union (KIU) in the Kurdistan Region of Iraq (KRI). Finally, the book’s main thesis is briefly discussed, and conclusion is drawn on the implication of Islamic brand of religious nationalism in the Middle East in general and Kurdistan Region of Iraq in particular.